Vibration Attenuation in Particle Mixer Using Magnetorheological Damping Technology to Mitigate the Brazil Nut Effect - Kwon Joong Son (Machines, 2025)
In industrial particle mixing processes, vibrations can intensify the Brazil nut effect (BNE), resulting in larger particles ascending, which contributes to vertical segregation based on particle size differences. These vibrations arise due to mass imbalance, motor functioning, and external disturbances, which negatively influence the efficiency of mixing. This research employs magnetorheological (MR) damping technology to reduce vibration-induced particle separation and consequently diminish the BNE. A drum mixer with an integrated MR damper was designed and constructed for experimental purposes, and its effectiveness in reducing vibrations was evaluated. Furthermore, simulations using the discrete element method (DEM) were performed to study the decrease in the BNE in different vibration settings. The results demonstrated that MR damping effectively decreased vibration levels, which significantly diminished the BNE and maintained the consistency of particle mixing. This study demonstrates the potential of MR damping as a practical solution to enhance mixing performance in industrial applications.